Effect of Equivalence Ratio on the Rice Husk Gasification Performance Using Updraft Gasifier with Air Suction Mode - Hendriyana, Hendriyana (Universitas Negeri Semarang, 2020)
Rice husk is the waste from agriculture industries that has high potential to produce heat and electricity through the gasification process. Air suction mode is new development for updraft rice husk gasification, where blower are placed at output of gasifier. The objective of this research is to examine these new configuration at several equivalence ratio. The equivalence ratio was varied at 32% and 49% to study temperature profile on gasifier, producer gas volumetric flow rate, composition of producer gas, producer gas heating value, cold gas efficiency and carbon conversion. The time needed to consume rice husk and reach an oxidation temperature of more than 700oC for equivalence ratio of 49% is shorter than 32%. Producer gas rate production per unit weight of rice husk increase fromÃ‚Â 2.03 Nm3/kg and 2.36 Nm3/kg for equivalence ratio of 32% and 49%, respectively. Composition producer gas for equivalence ratio of 32% is 17.67% CO, 15.39% CO2, 2.87% CH4, 10.62% H2 and 53.45% N2 and 49% is 19.46% CO, 5.94% CO2, 0.90% CH4, 3.46% H2 and 70.24% N2. Producer gas heating value for equivalence ratio 32% and 49% is 4.73 MJ/Nm3 and 3.27 MJ/Nm3, respectively. Cold gas efficiency of the gasifier at equivalence ratio 32% is 69% and at 49% is 55%.